Empagliflozin Treatment Is Associated With Improvements in Cardiac Energetics and Function and Reductions in Myocardial Cellular Volume in Patients With Type 2 Diabetes - Sharmaine Thirunavukarasu; Nicholas Jex; Amrit Chowdhary; Imtiaz Ul Hassan; Sam Straw; Thomas P. Craven; Miroslawa Gorecka; David A. Broadbent; Peter Swoboda; Klaus K. Witte; Richard M. Cubbon; Hui Xue; et al. (2021)
Sodium–glucose cotransporter 2 (SGLT2) inhibitors reduce the risk of major adverse cardiovascular (CV) events and hospitalization for heart failure (HF) in patients with type 2 diabetes (T2D). Using CV MRI (CMR) and 31P-MRS in a longitudinal cohort study, we aimed to investigate the effects of the selective SGLT2 inhibitor empagliflozin on myocardial energetics and cellular volume, function, and perfusion. Eighteen patients with T2D underwent CMR and 31P-MRS scans before and after 12 weeks’ empagliflozin treatment. Plasma N-terminal prohormone B-type natriuretic peptide (NT-proBNP) levels were measured. Ten volunteers with normal glycemic control underwent an identical scan protocol at a single visit. Empagliflozin treatment was associated with significant improvements in phosphocreatine-to-ATP ratio (1.52 to 1.76, P = 0.009). This was accompanied by a 7% absolute increase in the mean left ventricular ejection fraction (P = 0.001), 3% absolute increase in the mean global longitudinal strain (P = 0.01), 8 mL/m2 absolute reduction in the mean myocardial cell volume (P = 0.04), and 61% relative reduction in the mean NT-proBNP (P = 0.05) from baseline measurements. No significant change in myocardial blood flow or diastolic strain was detected. Empagliflozin thus ameliorates the “cardiac energy-deficient” state, regresses adverse myocardial cellular remodeling, and improves cardiac function, offering therapeutic opportunities to prevent or modulate HF in T2D.